Lugol's solution and Gentian violet eradicate methicillin‐resistant Staphylococcus aureus biofilm in skin wound infections. Issue 1 (28th May 2022) - Grønseth, Torstein; Ovchinnikov, Kirill V.; Carlsen, Harald; Benth, Jūratė Šaltytė; Diep, Dzung B.; von Unge, Magnus; Silvola, Juha T.
Abstract: The study aimed to evaluate the antibacterial efficacy of Lugol's solution 5% and Gentian violet 1% against methicillin‐resistant Staphylococcus aureus (MRSA) biofilm in vivo. The bactericidal efficacy for treatment of MRSA‐biofilm skin wound infection was tested in a murine model. Luciferase‐tagged S. aureus Xen31, a MRSA‐strain derived from S. aureus ATCC‐3359130, was used for infection. Wounds were made in the skin of mice and infected with MRSA. The mice were treated with Lugol's solution and Gentian violet. Application of the antimicrobial agents started 24 hours post infection and was repeated daily for five‐days. The antimicrobial effect on the biofilm bacteria was evaluated by measuring bioluminescence from MRSA daily for seven‐days. Lugol's solution and Gentian violet showed a significant reduction in luminescent signals from the first assessment day to all subsequent days ( P < .001). Lugol's solution and Gentian violet effectively eradicated MRSA in biofilm in vivo and could be alternatives or in addition to topical antibiotics when MRSA‐biofilm wound infection is suspected.